NEGATIVE PHENOMENA OF MYOCARDIAL CHEMOTHERAPY IN TUBERCULOSIS SPONDILITIS (Journal of Universal Science Research, 2025)
The peculiarities of the course of extrapulmonary forms of tuberculosis and the complexity of identifying the pathogen due to its small number in the pathological material require higher-technological laboratory studies. In cases of bone joint localization of a specific process, surgical intervention is necessary, with surgical material collected for cytology [7, 8].